Low-conductivity cooling liquid with good compatibility with brazing flux and preparation method of low-conductivity cooling liquid
By using a composite corrosion inhibitor in a low-conductivity coolant, combined with components such as ethylene glycol and ultrapure water, the problem of poor compatibility between the existing coolant and fluoroaluminate brazing flux is solved, and the effective corrosion and leakage prevention effect is achieved, and the service life is extended.
Patent Information
- Application Number
- CN202411417002.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-02-25
AI Technical Summary
The existing low conductivity coolant has poor compatibility with fluoroaluminate brazing flux welds, which cannot effectively inhibit ionic precipitation of welds, resulting in corrosion and leakage of the cooling system.
Complex corrosion inhibitors, including imidazolines, natural alkaloids and organosilane corrosion inhibitors, combined with components such as glycol and ultrapure water, are prepared to prepare coolant with a conductivity as low as 50μs/cm, and the effectiveness of the corrosion inhibitor is ensured through specific mixing and stirring conditions.
It achieves efficient compatibility with fluoroaluminate brazing welding, effectively prevents corrosion and leakage of the cooling system, and extends the service life of the cooling liquid and cooling system components.
Smart Images

Figure BDA0005079718090000051 
Figure BDA0005079718090000061 
Figure BDA0005079718090000071
Abstract
Description
Technical Field
[0001] The invention relates to a coolant and a preparation method thereof, and in particular to a low-conductivity coolant with good compatibility with a brazing flux and a preparation method thereof. Background Art
[0002] At present, most low-conductivity coolants adopt organic acid mixed with inorganic salt formula, and the conductivity is about 300μs / cm, which cannot meet the requirements of the current new energy vehicle cooling system. Therefore, it is necessary to provide a low-conductivity coolant, and its conductivity should usually be controlled below 100μs / cm. In addition to low conductivity, the coolant used in the power battery of new energy vehicles should also have a protective effect on various metals and non-metallic materials in the cooling system to prevent corrosion and leakage. At the same time, the coolant should also have good anti-scaling and antifreeze properties. The patent with publication number CN109810677A discloses a new energy vehicle coolant and a preparation method thereof. The coolant is composed of ethylene glycol, deionized water, phase change microcapsules, methyl amyl alcohol, benzotriazole, sodium hydroxide and sodium methyl silicate. The coolant has excellent low conductivity and excellent corrosion resistance to brass, steel, aluminum, etc., but its protection ability to fluoroaluminate brazing flux welds is poor, and it cannot inhibit the ion precipitation of fluoroaluminate brazing flux welds.
[0003] Therefore, according to the corrosion protection requirements of fluoroaluminate brazing flux welds, it is necessary to develop a low-conductivity coolant to inhibit the ions precipitated from the welds formed by fluoroaluminate brazing flux in components such as water-cooled plates and radiators. Summary of the invention
[0004] Purpose of the invention: The first purpose of the present invention is to provide a low-conductivity coolant with good anti-scaling, anti-freezing properties and good compatibility with brazing flux. The second purpose of the present invention is to provide a method for preparing the above-mentioned coolant.
[0005] Technical solution: The low-conductivity coolant with good compatibility with the brazing flux described in the present invention comprises the following components by mass percentage: antifreeze: 35-50%, organic base 0.1-1%, composite corrosion inhibitor composed of imidazoline corrosion inhibitor, natural alkaloid corrosion inhibitor and organic silane corrosion inhibitor 0.02-0.3%, defoamer: 0.0001-0.001%, dye: 0.0001-0.001%, solvent: balance, and the mass percentage of each component sums up to 100%.
[0006] Furthermore, the mass ratio of the oxazoline corrosion inhibitor, the natural alkaloid corrosion inhibitor and the organosilane corrosion inhibitor is 0.002-0.02:0.001-0.01:0.02-0.2.
[0007] Furthermore, the imidazoline corrosion inhibitor is one or more of decanoic acid imidazoline, nonanoic acid imidazoline, and octanoic acid imidazoline.
[0008] Furthermore, the natural alkaloid corrosion inhibitor is one or more of vincristine, arecoline, and arecoline.
[0009] Furthermore, the organic silane corrosion inhibitor is one or more of n-octyltriethoxysilane, isooctyltriethoxysilane, and n-octyltrimethoxysilane.
[0010] Furthermore, the antifreeze is ethylene glycol, the solvent is ultrapure water, preferably ultrapure water prepared by multi-stage OR reverse osmosis with EDI filtration equipment, with a conductivity of <1μs / cm, the organic base is one of monoethanolamine, diethanolamine, and triethanolamine; the defoaming agent is a GPE type polyether copolymerized with ethylene oxide and propylene oxide, with a molecular weight of 3000; the dye is azo dye disperse blue; and the brazing agent is a fluoroaluminate brazing agent.
[0011] The method for preparing the low conductivity coolant comprises the following steps:
[0012] (1) mixing an imidazoline corrosion inhibitor and a natural alkaloid corrosion inhibitor to obtain a solution A;
[0013] (2) mixing part of the solvent, the organic base, and the organosilane corrosion inhibitor to obtain solution B;
[0014] (3) After the remaining solvent and antifreeze are mixed, solution B and solution A are added, and then the dye and defoaming agent are added in sequence to obtain a low-conductivity coolant after mixing evenly.
[0015] Furthermore, in step (2), the mixing conditions are: stirring at 50-70°C for 5-10h; under this condition, the organosilane corrosion inhibitor can maintain a better degree of hydrolysis in solution B to ensure the metal corrosion inhibition performance of the coolant. Exceeding this temperature range will cause the organosilane to be over-hydrolyzed or incompletely hydrolyzed. When the hydrolysis is incomplete, the metal corrosion inhibition performance is reduced; if the hydrolysis temperature is too high, the organic amine is in danger of oxidation, resulting in a decrease in the system's reserve alkalinity. At this time, even if natural alkaloids are added to the compound, the stability of the coolant will decrease; in step (3), the mixing conditions are: stirring at 40-50°C for 30-100min; in step (3), the dye and defoamer need to be dissolved in a solvent in advance, and the amount of solvent used is 10 times or more of the mass of the dye and defoamer.
[0016] Principle of the invention: Among the compound corrosion inhibitors used in the present invention, the imidazoline corrosion inhibitor is an adsorption corrosion inhibitor, whose molecular structure has low energy and stable conformation, and is widely used to inhibit the corrosion of metals by acidic media. Its adsorption principle follows the Langmuir isothermal adsorption theory, and it is adsorbed on the metal surface in molecular form. The imidazoline molecule contains N=C double bonds and lone electrons on the N atom, which can covalently bind to the empty orbital of the metal periphery, so that the imidazole ring covalently acts parallel to the metal surface. The natural curling of its hydrophilic bond is conducive to the adsorption of lone electron pairs in nitrogen atoms or other active groups on the amino group on the metal surface, thereby protecting the metal. According to the principle of hard and soft acid and base, natural alkaloid corrosion inhibitors propose to use five-membered and six-membered heterocyclic organic bases with appropriate electronegativity to form a chelate structure at the interface between metal and antifreeze. The cyclic organic base substances are tightly clamped on the metal parts like the claws of a crab. This multi-dentate ligand bonding structure is more stable than general complexes, forming a strong protective film to mask metal ions, and using the synergistic and mutual solubility between the components to construct a weakly alkaline, low-conductivity, non-ionic coolant environment. While efficiently dissipating heat and preventing freezing at low temperatures, it can protect the metal parts and sealing parts of the cooling system to the greatest extent, achieving the effect of one-time addition and ultra-long-term use. Silane corrosion inhibitors can not only penetrate into the metal surface, react chemically with the metal, and form a dense protective film. It can also change the electrochemical properties of the metal surface and enhance the corrosion resistance of the metal, mainly by controlling the growth rate of the corrosion point. When the corrosive medium accumulates at the corrosion point without diffusion, the silane corrosion inhibitor can passivate the corrosion point again, thereby terminating the corrosion process. And it can form a protective film by self-assembly. This film not only provides a physical barrier, but also further enhances the corrosion resistance of the metal through chemical reactions.
[0017] The compound system of imidazoline corrosion inhibitor, natural alkaloid corrosion inhibitor and organosilane corrosion inhibitor, because a single corrosion inhibitor often contains only limited groups, it is difficult to fully utilize the active sites on the metal surface to form a thin film with high coverage. The silane film layer can only provide passive corrosion protection. When forming a film, the silane molecules tend to use the hydroxyl groups on the metal surface to form bonds. The resulting pores and defects allow corrosive ions to penetrate into the metal surface. The self-assembled film of a single corrosion inhibitor on the aluminum surface can only utilize limited active sites. The addition of imidazoline and alkaloids can play a role in connecting organic and inorganic components. The compounding of the three can make fuller use of the metal surface area and reduce the pores of the film layer, thereby inhibiting the ions that are precipitated from the welds formed by the fluoroaluminate brazing flux in components such as water-cooled plates and radiators, and effectively protecting the welds of the fluoroaluminate brazing flux.
[0018] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) All components in the coolant are non-ionic substances, and do not contain inorganic salts, organic carboxylic acids and other components with high conductivity. The conductivity is as low as 50μs / cm, which is only a few hundredths of the conductivity of the commonly used water-cooling medium. In an ultra-low conductivity environment, it can effectively slow down the corrosion of metal parts in the cooling system; (2) It has good compatibility with the weld of fluoroaluminate brazing flux, and can effectively prevent the corrosion of components such as aluminum alloy radiators, thereby extending the service life of components such as aluminum alloy radiators; (3) Imidazoline, organosilane and natural alkaloids are added to the composite corrosion inhibitor, so that it has excellent corrosion inhibition ability on the one hand, which can slow down the corrosion of corrosive substances on various metals such as copper, brass, steel, cast aluminum, 3003 aluminum, 4043 aluminum and 6063 aluminum, and meet the demand for corrosion inhibition ability in water-cooled plates; on the other hand, it has excellent scale inhibition ability, which can effectively reduce the formation of insoluble scale such as calcium carbonate, and avoid affecting production and processing. DETAILED DESCRIPTION
[0019] The present invention is further described below in conjunction with specific embodiments.
[0020] Example 1: The low-conductivity coolant with good compatibility with the brazing flux provided in this example comprises the following components in percentage by mass: ethylene glycol: 50.000%, monoethanolamine: 1.000%, imidazoline caprate: 0.02%, scopolamine: 0.01%, n-octyltriethoxysilane: 0.200%, GPE type polyether copolymerized with ethylene oxide and propylene oxide with a molecular weight of 3000: 0.001%, azo dye disperse blue: 0.001%, and ultrapure water: the balance.
[0021] The preparation method of the above-mentioned coolant is as follows:
[0022] (1) mixing imidazoline caprate and scopolamine in proportion to obtain solution A for standby use;
[0023] (2) adding part of ultrapure water and monoethanolamine in proportion to a reaction kettle, stirring, then adding n-octyltriethoxysilane, raising the temperature to 50-70° C., reacting for not less than 5 hours, obtaining solution B, cooling and setting aside;
[0024] (3) Add ultrapure water and polyester-grade ethylene glycol to a stirring kettle, stir and heat to 40-50° C., then add solution B obtained in step (2) and solution A obtained in step (1), stir for not less than 30 minutes, cool to room temperature, add a defoaming agent, and obtain a cooling liquid.
[0025] Example 2: The low-conductivity coolant with good compatibility with the brazing flux provided in this example comprises the following components in percentage by mass: polyester-grade ethylene glycol: 50.000%, diethanolamine: 1.000%, imidazoline nonanoate: 0.02%, vincristine: 0.01%, isooctyltriethoxysilane: 0.200%, ethylene oxide and propylene oxide copolymer GPE type polyether with a molecular weight of 3000: 0.001%, azo dye disperse blue: 0.001%, and ultrapure water: the balance.
[0026] The preparation method of the above cooling liquid is the same as that of Example 1.
[0027] Example 3: The low-conductivity coolant with good compatibility with the brazing flux provided in this example comprises the following components in percentage by mass: polyester-grade ethylene glycol: 50.000%, triethanolamine: 1.000%, imidazoline heptanoate: 0.02%, arecoline: 0.01%, n-octyltrimethoxysilane: 0.020%, GPE-type polyether copolymerized with ethylene oxide and propylene oxide with a molecular weight of 3000: 0.001%, azo dye disperse blue: 0.001%, ultrapure water, and the remainder.
[0028] The preparation method of the above cooling liquid is the same as that of Example 1.
[0029] Example 4: The low-conductivity coolant with good compatibility with the brazing flux provided in this example comprises the following components in percentage by mass: polyester-grade ethylene glycol: 35.000%, triethanolamine: 0.100%, imidazoline heptanoate: 0.002%, arecoline: 0.001%, n-octyltrimethoxysilane: 0.200%, ethylene oxide and propylene oxide copolymer GPE type polyether with a molecular weight of 3000: 0.0001%, azo dye disperse blue: 0.0001%, ultrapure water, and the remainder.
[0030] The preparation method of the above cooling liquid is the same as that of Example 1.
[0031] Example 5: The low-conductivity coolant with good compatibility with the brazing flux provided in this example comprises the following components in percentage by mass: polyester-grade ethylene glycol: 35.000%, diethanolamine: 0.100%, imidazoline nonanoate: 0.002%, vincristine: 0.001%, isooctyltriethoxysilane: 0.0200%, ethylene oxide and propylene oxide copolymer GPE type polyether with a molecular weight of 3000: 0.001%, azo dye disperse blue: 0.001%, and ultrapure water: the balance.
[0032] The preparation method of the above cooling liquid is the same as that of Example 1.
[0033] Comparative Example 1: Commercially available low-conductivity coolant, model BASF Glysantin G22.
[0034] Comparative Example 2: Commercially available low-conductivity coolant, model number is NE100.
[0035] Comparative Example 3: This comparative example is the coolant provided by Example 4 of patent CN109810677A.
[0036] Comparative Example 4: The difference from Example 1 is that the composition of the composite corrosion inhibitor is: 0.001% of imidazoline decanoate, 0.0005% of scopolamine, and 0.01% of n-octyltriethoxysilane.
[0037] Comparative Example 5: The difference from Example 1 is that only imidazoline decanoate is used as the corrosion inhibitor, and the dosage is 0.3%.
[0038] Comparative Example 6: The difference from Example 1 is that only scoparia alkali is used as the corrosion inhibitor, and the dosage is 0.2%.
[0039] Comparative Example 7: The difference from Example 1 is that the corrosion inhibitor is only n-octyltriethoxysilane, and the dosage is 2%.
[0040] The low conductivity coolants prepared in Examples 1 to 6 were subjected to freezing point, pH, reserve alkalinity, conductivity, static corrosion test, EPDM compatibility test, silicone rubber compatibility test, hard water resistance stability test and cycle bench test.
[0041] Static corrosion test (80℃, 336h, SH / T 0085): copper: ±2mg / piece; brass: ±2mg / piece; steel: ±2mg / piece; ZL101A cast aluminum: ±5mg / piece; 3003 aluminum: ±5mg / piece; 4043 aluminum: ±5mg / piece; 6063 aluminum: ±5mg / piece;
[0042] High temperature stability (135℃, 168h, SH / T 0620): mass change: ±1.0; solution precipitation after the test ≤0.05mL;
[0043] EPDM compatibility (80℃, 168h h, GB / T 1690): Hardness change: ±5IRHD; Volume change rate ±5%; Break tensile strength change rate ±15%; Break elongation change rate ±30%;
[0044] Silicone rubber compatibility (80℃, 168h h, GB / T 1690): Hardness change: ±5IRHD; Volume change rate ±5%; Break tensile strength change rate ±15%; Break elongation change rate ±30%;
[0045] Hard water resistance (90℃±2℃, 336h±2h, Appendix D of GB 29743.1): No precipitation or suspended matter.
[0046] The test results are shown in Table 1, which show that the low conductivity coolant of the present invention has the properties of low conductivity, metal corrosion protection, non-metal compatibility, anti-scaling, hard water resistance, etc. From the experimental data, it can be seen that the difference of ten times in the amount of corrosion inhibitor has an impact on conductivity, pH, reserve alkalinity, rubber compatibility and cycle bench test, but has no effect on static corrosion.
[0047] Table 1 Performance test of the coolant prepared in Example 1-Example 6
[0048]
[0049]
[0050] The performance tests were conducted on the low conductivity coolants prepared in Examples 1 to 6 and the coolants in Comparative Examples 1 to 3. The solutions of the examples and comparative examples were tested according to the test method in Appendix A of T / CAS48-2021, and a standard test piece of 3003 aluminum welded with fluoroaluminate brazing flux was added. The weld width was 1 mm, located in the middle of the test piece and parallel to the length of the test piece. The conductivity of the low conductivity coolant sample and the metal corrosion of the test piece sample were tested. The specific test results are shown in Table 2. The standard test piece corrosion test of 3003 aluminum welded with fluoroaluminate brazing flux represents the compatibility of the fluoroaluminate brazing flux weld.
[0051] Compared with Example 1, Comparative Example 4 reduces the amount of each corrosion inhibitor, and all are not within the optimal ratio. Although the conductivity is relatively high, the amount is insufficient, resulting in the ineffective protection of each metal and corrosion. Compared with Example 1, Comparative Example 5 uses only 15 times the amount of imidazoline decanoate, which not only increases the conductivity, but also can only protect copper and steel metals, but cannot effectively protect aluminum. Compared with Example 1, Comparative Example 6 uses only 30 times the amount of scopolamine, which cannot effectively protect aluminum. Compared with Example 1, Comparative Example 7 uses only 10 times the amount of n-octyltriethoxysilane. Although it protects aluminum metal, it cannot protect copper and steel well, and corrosion occurs in 3003 aluminum brazed with fluoroaluminate. Because a single corrosion inhibitor often contains only limited groups, it is difficult to fully utilize the active sites on the metal surface to form a thin film with a high coverage rate. Therefore, a composite system of imidazoline corrosion inhibitors, natural alkaloid corrosion inhibitors and organosilane corrosion inhibitors is needed. The combination of the three can make more full use of the metal surface area and reduce the porosity of the film layer, thereby inhibiting the formation of ions precipitated from the welds of fluoroaluminate brazing flux in components such as water-cooled plates and radiators, and effectively protecting the welds of fluoroaluminate brazing flux.
[0052] Table 2 Static corrosion test data of different coolants
[0053]
[0054] In summary, the low conductivity coolant of the present invention has excellent low conductivity performance, low conductivity retention and fluoroaluminate brazing flux weld compatibility, thereby ensuring the normal operation of the battery engine, significantly reducing the precipitation of ions, extending the service life of the coolant, and effectively extending the service life of components such as the aluminum alloy radiator.
Claims
1. A low conductivity coolant with good compatibility with brazing flux, characterized in that: Calculated by mass percentage, it includes the following components: Antifreeze: 35-50%, organic base 0.1-1%, compound corrosion inhibitor composed of imidazoline corrosion inhibitor, natural alkaloid corrosion inhibitor and organic silane corrosion inhibitor 0.02-0.3%, defoamer: 0.0001-0.001%, dye: 0.0001-0.001%, solvent: balance, the mass percentage of each component is 100%.
2. The low conductivity coolant according to claim 1, characterized in that: The mass ratio of the oxazoline corrosion inhibitor, the natural alkaloid corrosion inhibitor and the organosilane corrosion inhibitor is 0.002-0.02:0.001-0.001:0.02-0.
2.
3. The low conductivity coolant according to claim 1, characterized in that: The imidazoline corrosion inhibitor is one or more of imidazoline decanoate, imidazoline nonanoate, and imidazoline octanoate.
4. The low conductivity coolant according to claim 1, characterized in that: The natural alkaloid corrosion inhibitor is one or more of vincristine, arecoline and arecoline.
5. The low conductivity coolant according to claim 1, characterized in that: The organic silane corrosion inhibitor is one or more of n-octyltriethoxysilane, isooctyltriethoxysilane and n-octyltrimethoxysilane.
6. The low conductivity coolant according to claim 1, characterized in that: The antifreeze agent is ethylene glycol, the solvent is ultrapure water, and the organic base is one of monoethanolamine, diethanolamine and triethanolamine.
7. The low conductivity coolant according to claim 1, characterized in that: The defoamer is a GPE type polyether copolymerized with ethylene oxide and propylene oxide; and the dye is azo dye disperse blue.
8. The low conductivity coolant according to claim 1, characterized in that: The brazing flux is a fluoroaluminate brazing flux.
9. A method for preparing the low conductivity coolant according to claim 1, characterized in that: The following steps are involved: (1) mixing an imidazoline corrosion inhibitor and a natural alkaloid corrosion inhibitor to obtain a solution A; (2) mixing part of the solvent, the organic base, and the organosilane corrosion inhibitor to obtain solution B; (3) After the remaining solvent and antifreeze are mixed, solution B and solution A are added, and then the dye and defoaming agent are added in sequence to obtain a low-conductivity coolant after mixing evenly.
10. The preparation method according to claim 9, characterized in that: In step (2), the mixing conditions are: stirring at 50-70°C for 5-10 hours; in step (3), the mixing conditions are: stirring at 40-50°C for 30-100 minutes.
Citation Information
Patent Citations
New energy vehicle cooling liquid and preparation method thereof
CN109810677A